Devotion [videorecording (DVD)] - Crane, Jake; Stewart, Jonathan A.H; Luckinbill, Thad, 1975-; Majors, Jonathan, 1989-; Powell, Glen, 1988-; Jackson, Christina (Actress); Kagasoff, Daren, 1987-; Jonas, Joe, 1989-; Neville, Spencer; Hargrove, Nick; Platt, Boone; Cross, Joseph, 1986-; et al. (Paramount Pictures, 2023)
Elite fighter pilots Jesse Brown and Tom Hudner become the U.S. Navy's most celebrated wingmen during the Korean War.